Reconfiguração de redes de distribuição utilizando algoritmo de Busca Tabu - Pinheiro Filho, Luiz Otávio (2022)
This work presents a method for reconfiguration of distribution networks that combines the Tabu Search algorithm and the concept of Electric Distance to the software OpenDSS, which calculates power flow in distribution systems. The proposed method has an initial solution generation system based on Electric Distance capable of obtaining a good solution to the problem with very low computational cost, using only the network configuration for the calculation. The proposed work also presents a neighborhood generation method for the Tabu Search algorithm, which is innovative in the technical literature, capable of providing a constant downward trajectory in relation to the losses of the distribution system. The developed algorithm aims to minimize losses in the distribution network while respecting operational restrictions such as radiality, voltage and current limits, among others. For that, a program was created in the programming language Python that integrates OpenDSS to the proposed algorithm. The algorithm was tested in four systems widely used in the literature: 33-Bus, 69-Bus, 94-Bus and 135-Bus; the last two being real systems. The test results were compared with results from other techniques proposed in the literature, proving that the proposed algorithm achieves the intended results and solutions more efficiently, faster and with greater performance compared to other methods.